2013
DOI: 10.1073/pnas.1303627110
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzee responders still behave like rational maximizers

Abstract: The ultimatum game (1) is a powerful and widely used test of bargaining behavior that has only recently been applied to nonhuman animals (2-4). The key feature of this game is the power the responder has; the threat of rejections-the ultimatum-typically induces proposers to be more generous than they would be otherwise. Proctor et al. (4) In Proctor et al. (4), the conclusion that chimpanzees play an ultimatum game was based on an exclusive focus on proposers. The four proposers showed a preference for smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…This behavior appears non-adaptive because receiving some food is better than receiving no food. There have been several discussions about inequality aversion in non-human animals (Chen and Santos, 2006;Jensen et al, 2013;Massen et al, 2012;Sheskin et al, 2014). These laboratory investigations showed that social inequality aversion decreases the rewarding value of food, while the present experiment showed social inequality aversion increased stress by restraint.…”
Section: Discussionmentioning
confidence: 41%
“…This behavior appears non-adaptive because receiving some food is better than receiving no food. There have been several discussions about inequality aversion in non-human animals (Chen and Santos, 2006;Jensen et al, 2013;Massen et al, 2012;Sheskin et al, 2014). These laboratory investigations showed that social inequality aversion decreases the rewarding value of food, while the present experiment showed social inequality aversion increased stress by restraint.…”
Section: Discussionmentioning
confidence: 41%
“…As the concept of equal opportunity seems to be a cultural product rather than an evolutionary trait, then humans may alone value equality of opportunity, while other primates may share the bases of the preference for equality of outcome. Recent research suggests that a few animals such as dogs and primates exhibit preference for equality of outcome (Brosnan, 2006;Proctor et al, 2013;Range et al, 2009), although the true existence of preference for equal outcome in nonhuman species is still under debate (Bräuer et al, 2006;Jensen et al, 2013). Do non-human animals understand equality of opportunity -for example, do they share a tool and prefer equalizing opportunity to use it, rather than equalizing the amount of food obtained by the tool use?…”
Section: Equality Of Outcome Vs Equality Of Opportunity: Possible DImentioning
confidence: 98%
“…Fairness is a core part of human social life (Haidt & Joseph, ; Henrich et al., ; Rozin, Lowery, Imada, & Haidt, ; Shweder, Much, Mahapatra, & Park, ). Indeed, fairness may be a specifically human concern (e.g., Jensen et al., ; Silberberg, Crescimbene, Addessi, Anderson, & Visalberghi, ; Sheskin & Santos, ), as even the strongest evidence for concerns about fairness in nonhumans is limited to cases where the animal itself (not another) gets cheated (e.g., Brosnan & De Waal, ; Brosnan & Waal, ; Hopper, Lambeth, Schapiro, Bernacky, & Brosnan, ; Proctor, Williamson, de Waal, & Brosnan, ). Fairness may be a characteristic part of human social life because humans show high levels of joint activity (Clutton‐Brock, ) and often have the option to pursue joint projects only with others who have a proven history of fair behavior (Baumard, André, & Sperber, ).…”
Section: The Slow Emergence Of Costly Fair Behaviormentioning
confidence: 99%